2017
DOI: 10.1149/08008.0019ecst
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructure of HT-PEFC Electrodes Investigated with Scattering Methods

Abstract: The nanostructure of the electrode layer of a HT-PEFC is studied with neutron and X-ray small-angle scattering techniques. The different contrasts of the two probes provide a view on different aspects of the electrode layer. In combination with contrast variation by H-D isotope exchange further insight into the distribution of the different components on length scales in the range of 1-100 nm is obtained. An outlook shows the perspectives of scattering techniques for studying proton diffusion in such heterogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Schematic picture of a HT-PEFC with proton conducting polymer membrane surrounded by the electrode layers. The zoom on the right shows a sketch of the electrode layer consisting of Pt catalyst particles on a carbon-PTFE support with phosphoric acid in the remaining space[55]…”
mentioning
confidence: 99%
“…Schematic picture of a HT-PEFC with proton conducting polymer membrane surrounded by the electrode layers. The zoom on the right shows a sketch of the electrode layer consisting of Pt catalyst particles on a carbon-PTFE support with phosphoric acid in the remaining space[55]…”
mentioning
confidence: 99%
“…The structure of HT-PEFC catalyst layers has been analyzed with SAXS, SANS and transmission electron microscopy (TEM) with samples of the same kind (20% and 60% Pt) [19,25,26]. In these publications we have shown that the combination of different scattering methods highlights different parts of the sample.…”
Section: Discussionmentioning
confidence: 99%
“…In the SANS regime, such experiments have been presented in Ref. [25]. This is especially useful for such heterogeneous systems as electrode layers.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of HT-PEFC catalyst layers has been analyzed with SAXS, SANS and transmission electron microscopy (TEM) with samples of the same kind (20 and 60 % Pt) [13,19,20]. In these 2 instances of the Beaucage model, with R g,0 of about 10 Å from the Pt particles, and a larger length scale R g,1 500 Å of the supporting structure, with a fractal power law decay with an exponent P close to 4 indicating a compact structure.…”
Section: Discussionmentioning
confidence: 99%